Influence of Elevated Temperatures on some Bactericidal Parameters (Journal of Science and Technology, 2016)
The current work revealed a pattern that showed that the general performance of bactericides at elevated temperature was strikingly different from that at ambient temperatures. Increases in temperature caused far less dramatic changes in bactericidal activity than they did at low temperatures; figures of merit (bacteriedal parameters) that reflect such activity changes generally declined persistently. Rises in temperature had the effect of masking clear distinctions in relative performance that form the basis of evaluation of bactericides for selection, procurement and use. Heat application ultimately seemed to veer all the 'types of bactericides studied towards a point of uniform activity where all bactericides would exert the same activity i.e., phenol coefficient 1.0. By extrapolation this point of isoactivity was expected to occur at a critical temperature at or slightly above 1610'C. The significance of the observation is that at the critical temperature, the type of bactericide, or concentration used in the process of sterilization by heating with a bactericide would be of little relevance to the ultimate success of sterilization as heat would be the predominant factor in microbial destruction.